2023
DOI: 10.1080/14756366.2023.2224944
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, seasonal variation and antiaging activities of essential oil from Callistemon subulatus leaves growing in Egypt

Omyma Rabie,
Heba A. S. El-Nashar,
Taghreed A. Majrashi
et al.

Abstract: Callistemon is an aromatic genus of flowering plants belonging to family Myrtaceae. The essential oils of C. subulatus leaves were collected in four seasons and analyzed using GC/MS. The oils demonstrated monoterpenes as the predominant class. Eucalyptol was the main component in all seasons; summer (66.87%), autumn (58.33%), winter (46.74%) and spring (44.63%), followed by α -pinene; spring (31.41%), winter (28.69%), summer (26.34%) and autumn (24.68%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Nitta and his co-authors isolated potent histidine decarboxylase inhibitors namely, quercetin 3-O-β-D-glucuronide 6''-methyl ester (14) and quercetin 3-O-(2-O-galloyl)glucoside (15) from the ethyl acetate extract of P. racemose berries. [43] Another phytochemical study on the methanol extract revealed isolation of two flavonoid glycosides namely, quercetin 3-O-β-D-glucuronopyranoside (16), and quercitrin (17), coupled with a new dihydrokaempferol namely, 3-carboxy-6,8-di-C-methyl-dihydrokaempferol 3-O-β-D-glucopyranoside (18).…”
Section: Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitta and his co-authors isolated potent histidine decarboxylase inhibitors namely, quercetin 3-O-β-D-glucuronide 6''-methyl ester (14) and quercetin 3-O-(2-O-galloyl)glucoside (15) from the ethyl acetate extract of P. racemose berries. [43] Another phytochemical study on the methanol extract revealed isolation of two flavonoid glycosides namely, quercetin 3-O-β-D-glucuronopyranoside (16), and quercitrin (17), coupled with a new dihydrokaempferol namely, 3-carboxy-6,8-di-C-methyl-dihydrokaempferol 3-O-β-D-glucopyranoside (18).…”
Section: Flavonoidsmentioning
confidence: 99%
“…[12] The name Pimento was derived from the Spanish word pimienta, which means pepper and was dubbed as such incorrectly as stated above because the name "Pimento" is reserved for Capsicum annum, which is a variety of red pepper. [3,13,14] Pimenta pseudocaryophyllus has synonyms such as 'carveiro', 'cataia' and 'louro-cravo',…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of chemotherapy drugs used to treat PCa over the past four decades are derived from herbs; Moreover, isolated compounds from herbal plants are presently being investigated to provide different lead structures, which can be used as frameworks to make new and more potent anticancer drugs (Abdelghffar et al, 2021;Mann, 2002). These compounds may be able to fight cancer because they act as antioxidants, get rid of free radicals, and stop enzymes in cells from changing DNA Jamaddar et al, 2023;Rabie et al, 2023). These characteristics are expected to protect against somatic mutations and adverse epigenetic DNA changes when taken together (Reddy et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our ancestors were totally dependent on a wide variety of plants to treat themselves from disease until the introduction of synthetic medicines. It is found that almost 2000 racial groups all over the world have their own unique medical understanding and experience. , This is because some vital components that possess antioxidant and anti-inflammatory properties are used in certain physiologic conditions . There were 90 drugs that are commercially available or approved worldwide in the period of 1982 to 2002, and 79% of them were from natural sources. Still a large portion of the population use medicinal plants as primary source to treat different diseases such as fever, pain, inflammation, diarrhea, and many other illnesses. , …”
Section: Introductionmentioning
confidence: 99%